ЛИСОНИЙ ҲОДИСАЛАРГА ПРАГМАЛИНГВИСТИК ВА ЛИНГВОПРАГМАТИК ЁНДАШУВ ҲАҚИДА - Эрназарова, М.С. (SCIENCE and SOCIETY, 2021)
The article discusses the issue of linguistic pragmatism or the relationship of pragmatic linguistics to linguistics and pragmatics, the need to clarify the object of their study, the definition of their research objects because pragmatic linguistics in science does not differ from linguistic pragmatism. Each event was analyzed according to the principle of unbiased naming.
Keywords: linguistic phenomenon; pragmalinguistics; linguapragmatics; pragmatics; semiotics; addresse; addressee; communication system; linguistic system